\(Ophiocordyceps xuansonae\) a novel species of genus \(Ophiocordyceps\) in Vietnam - Viet, Nguyen Dinh; Lam, Truong Xuan; Lam, Duong Minh (Academia Journal of Biology, 2023)
The Ophiocordyceps is an important globally distributed genus that includes over 239-recorded species. Many species of the genus are famous for their significance in ecology, agriculture and pharmaceuticals. There have been 12 species of genus Ophiocordyceps found in Vietnam. In this study, the samples of Ophiocordyceps parasitizing the larva of order Lepidoptera at Xuan Son National Park in Phu Tho province were collected and characterized using both morphology and molecular analyses. The morphology comparison and ITS sequence analysis revealed that the fungus belongs to a new species of Ophiocordyceps. The paper presents the morphological and molecular description of the species.